The relationship between emotional intelligence and leadership styles in the South African petrochemical industry - Maggie Pillay (SA Journal of Industrial Psychology, 2013)
Orientation: Although research on emotional intelligence in the context of leadership has remained a recurrent area of interest in theory and practice during the past decade, ongoing debate continues regarding the contribution of emotional intelligence to the understanding of leadership. Research purpose: The aim of this study was to determine the relationship between self-reported emotional intelligence and leadership styles in a South African context and to determine whether emotional intelligence can predict an effective leadership style.